2020
DOI: 10.1016/j.dib.2020.106177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge, impacts and government intervention strategies during the COVID – 19 pandemic in Nigeria

Abstract: The SARS-CoV-2 is a novel strain of coronavirus which is ravaging many countries, and this has become a global public health concern. With the increasing number of COVID-19 confirmed cases and deaths in Nigeria, the pandemic has led to massive public reactions. This data attempted to evaluate the knowledge, impacts, and government intervention during the pandemic. An online survey was conducted using a questionnaire shared via social media using a Snowball sampling technique. The data were analyzed using descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The level of attitude in the articles included in this systematic review ranged from as low as 59% (18) to as high as 94% (20). The ndings of this review have also revealed that age, gender, level of education, background, and nationality were reported to have had a signi cant impact on the attitude towards community-based COVID-19 preventive measures.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The level of attitude in the articles included in this systematic review ranged from as low as 59% (18) to as high as 94% (20). The ndings of this review have also revealed that age, gender, level of education, background, and nationality were reported to have had a signi cant impact on the attitude towards community-based COVID-19 preventive measures.…”
Section: Discussionmentioning
confidence: 80%
“…Age (18-39 years), education (college/bachelors), and background of respondents were factors in uencing knowledge levels (19). While in a study conducted by (20) in Nigeria, the knowledge of the outbreak of COVID-19 was in uenced by the age (p < 0.05), gender (p < 0.05), level of education (p < 0.05), marital status (p < 0.05) and employment status (p < 0.05). In a study conducted in Uganda by Usman et al (2020)(4), found that the percentage score among those having their phones connected and those not having connected to the internet on knowledge was 77.00% and 74.53%, respectively.…”
Section: Level Of Kap On Community-based Interventions For Preventingmentioning
confidence: 96%
See 3 more Smart Citations